Comparison of Lipid Profiles among the Women with or without Oral Contraceptive Pill Users - Sultana, Abida; Rahman, Shamima; Alam, Al Mamun Mahbub (Journal of Current and Advance Medical Research, 2018)
Background: The label of Lipid profiles may vary among the oral contraceptive pill users and non-users. Objective: This present study was undertaken to compare the lipid profiles among women with or without OCP users. Methodology: This comparative cross-sectional study was conducted in the Department of Obstetrics & Gynaecology and Family Planning Department in collaboration with the Biochemistry Department at Sir Salimullah Medical College & Mitford Hospital, Dhaka from June 2009 to May 2010 for a period of one (1) year. Women using low-dose OC pill for more than one year were considered as group A, while women not using low-dose OC pill were taken as group B of the study. Lipid profiles were performed in the laboratory in the fasting state from blood. Result: In this study 80 subjects were recruited for this study of which 40 women in group A and the rest 40 women were in group B. Over three-quarter (77.5%) of the group A had raised serum total cholesterol as opposed to only 17.5% of the group B (p < 0.001). Raised serum triglyceride and raised LDL-cholesterol were also significantly higher in the group A than those in the group B (p=0.019 and p<0.001 respectively). Majorities of the subjects in the group A (87.5%) and in the group B (90%) exhibited low HDL with no significant difference between the groups (p=0.556). Conclusion: In conclusion serum total cholesterol, triglyceride and LDL-cholesterol are significantly associated among the women who use low dose OCP than without OCP users. Journal of Current and Advance Medical Research 2016;3(2):43-46